Políticas públicas para a implementação dos objetivos de desenvolvimento sustentável no município de Itabaiana, Sergipe - Ferreira, Mateus Matos (2021)
The current scenario highlights the need for initiatives that minimize society's environmental problems. In view of this panorama, it is important to align the actions developed by different social actors, whether public authorities in their different spheres, private initiative, nongovernmental organizations and organized civil society with actions that enable progress at the local level and in a global perspective. The Agenda 2030 was established by the United Nations in 2015, with the endorsement of 193 member countries, contemplating 17 different objectives that permeate the sphere of economic growth, social development and environmental preservation. The aim of this research will be to highlight the importance of monitoring actions aligned with the Sustainable Development Goals (SDGs) at the municipal level. In addition, the aim was to determine public policies that ensure the implementation of the SDGs in Itabaiana, identifying the prioritized areas. Thereunto, I analyzed actions and projects developed and published in the Official Gazette of the Municipality of Itabaiana, State of Sergipe, an open and accessible channel of communication between the municipal administration and the population, in the period from January 2016 to December 2020. To meet the proposed objectives, I carried out a Content Analysis and the corpus of this research consisted of 1191 editions of the Official Gazette, which totaled 26228 pages. In this sense, the data I obtained was submitted to different stages, namely: pre-analysis, coding, categorization and socialization of the results. Upon analysis, I found 147 actions mentioned in the Official Gazette. 19.32% involved only 1 SDG, while 42.04% of the actions are linked to 2 or 3 SDGs and 38.64% of the actions involved more than 3 SDGs. These results demonstrate the interdisciplinary nature of the Agenda 2030, which enables the involvement of different sectors of public or private power in favor of its goals. Therefore, the Agenda 2030 associated with the actions of the public power can provide a diagnosis that helps the insertion and territorialization of the SDGs at the municipal level.